Estudo da reação foto-fenton induzida por complexos ferricitrato para o tratamento de lixiviados de aterros sanitários - Diel, Taís Regina (2015)
Photo-Fenton reactions induced by ferricitrate complex applied to the treatment of sanitary landfill leachate (SLL), was studied. Using a lab-scale photo-reactor with artificial UV-light source, photo-Fenton reactions and derivations (photolysis, Fenton, photo-Fenton and ferricitrate), on the decolourisation and aromatic compounds removal were evaluated. Such reactions mediated at a pH of the solution 2.8, present some limitations such as: (i) precipitation and/or volatilization of humic acids in acidification steps, (ii) a partial precipitation of ferric ions complex with the organic pollutants present in SLL; resulting in absorbance removal at 254 nm as well as decolourisation, not represented effective oxidations. However, using ferricitrate reaction mediated by pH of the solution 6, was possible eliminated the acidification step, keeping the pollutants and iron ion soluble resulting in best oxidations rate. Probably due the stability and solubility associated to ferricarboxylates such as ferricitrate, as well as the increase of photo-sensibility. After, the main operating parameters of ferricitrate reaction such as pH of the solution, iron(III):citric acid concentrations, H 2 O 2 consumed and amount of energy UV required were investigated. The best results were obtained using: pH of the solution 6.0, 100 mg Fe(III):citric acid, consuming approximately 64 mM of H 2 O 2 and ≈ 9 kJ UV L -1 required; leading a ≈ 70% and 65% decolourisation and aromatic compounds removal, respectively. In such conditions, the efficiencies of organic contents reduction as: COD (≈ 39%), dissolved organic carbon (DOC) (≈ 30%) and total dissolved nitrogen (TDN) (≈ 25%) were satisfactory, and maintaining BOD 5 (≈ 30%) probably improving the treated in terms of SLL- biodegradability (BOD 5 /COD ratio).